Komunikasi Pemasaran Bolu Amor Sukabumi dalam Meningkatkan Brand Awarenessdi Masa Pandemi Covid-19 - Affan Neskisyah Ramadhan Neskisyah; Melisa Agustina (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
Bolu Amor Sukabumi implemented Integrated Marketing Communication to increase brand awareness during the Covid-19 pandemic. This research describes Bolu Amor Sukabumi's marketing communication strategy in strengthening brand awareness. The concept of Integrated Marketing Communication (IMC) was used as the basis of this research, involving various marketing activities. A qualitative method with a descriptive approach was used, as well as purposive sampling for the selection of four main informants. The research revealed six elements of integrated marketing communication implemented by Bolu Amor Sukabumi. First, in the advertising aspect, Bolu Amor Sukabumi focuses on the use of posters, banners, and social media to reach the audience. Second, the Publicity and Public Relations aspect involves collaboration with the wider community, although publicity still needs to be improved. Third, Sales Promotion attracts customers through various attractive promotions. Fourth, Direct Marketing utilizes electronic shopping and practical payment systems. Fifth, Event and Experience involves sponsorship of government activities, schools, charity events, and community empowerment. Sixth, Online and Social Media Marketing involves platforms such as Instagram, Facebook, and TikTok, with a dedicated team producing unique content and attractive designs. In conclusion, Bolu Amor Sukabumi adopted IMC strategies with various approaches to strengthen brand awareness amidst the pandemic.